Second Opinions: Negotiating Agency in Online Mothering Forums. Issue 4 (December 2021) - Aston, Megan; Price, Sheri; Hunter, Andrea; Sim, Meaghan; Etowa, Josephine; Monaghan, Joelle; Paynter, Martha
Study background: Online forums and other virtual communities are an increasing source of postpartum support and information for first-time mothers. However, there is little evidence about how new mothers in Canada access and use online resources. Purpose: The purpose of this study was to examine how first-time mothers accessed information and support both online and off-line during the first six months postpartum and how their experiences were constructed through social and institutional discourses. Methods: A qualitative feminist poststructuralist approach was used to analyze an online discussion board with first-time mothers in Nova Scotia. Results: Mothers who used the online discussion board experienced a sense of community with other mothers where empathy and encouragement were integral to the ways in which information and support were shared. "Weak ties" (with strangers) were important and led to the following themes: (a) empathy, encouragement, and information; (b) socialization; (c) blurring the boundaries of online and off-line networks; and (d) Developing community. Conclusions: These online forums offer insight for health professionals looking to improve mothers' care postpartum and point to a need to foster spaces for new mothers to talk to each other.